Using the TGA-DSC-IR-GCMS Combined System and TL-9000 Transfer Line for the Analysis of Organic Objects - Kossko, I.O.; Pashin, D.M.; Valitov, M.I. (Science and Innovation, 2024)
The use of combined system of thermal gravimetric analysis, differential scanning calorimetry, IR-Fourier spectroscopy, gas chromatography, and mass spectrometry allows the researchers both to identify and to separate various components of organic objects. The installation makes it possible to carry out comprehensive complementary express analysis of objects at the temperature up to 1000 °С.